2022
DOI: 10.1186/s40478-022-01349-0
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue-specific and repeat length-dependent somatic instability of the X-linked dystonia parkinsonism-associated CCCTCT repeat

Abstract: X-linked dystonia-parkinsonism (XDP) is a progressive adult-onset neurodegenerative disorder caused by insertion of a SINE-VNTR-Alu (SVA) retrotransposon in the TAF1 gene. The SVA retrotransposon contains a CCCTCT hexameric repeat tract of variable length, whose length is inversely correlated with age at onset. This places XDP in a broader class of repeat expansion diseases, characterized by the instability of their causative repeat mutations. Here, we observe similar inverse correlations between CCCTCT repeat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The presence of expansion could be a further modulator of this effect within the nervous system. Importantly, given what is seen in a mouse model of the FXDs 44 , and in patients with other repeat expansion diseases 45 , 46 , the degree of expansion may be higher in the brain compared to peripheral blood from which this study’s samples were obtained. As we previously showed, given that expansion increases with the number of CGG repeats and that the latter correlates with FMR1 mRNA levels, the presence of expansion could be a marker for elevated mRNA related toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of expansion could be a further modulator of this effect within the nervous system. Importantly, given what is seen in a mouse model of the FXDs 44 , and in patients with other repeat expansion diseases 45 , 46 , the degree of expansion may be higher in the brain compared to peripheral blood from which this study’s samples were obtained. As we previously showed, given that expansion increases with the number of CGG repeats and that the latter correlates with FMR1 mRNA levels, the presence of expansion could be a marker for elevated mRNA related toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Although two independent genome-editing studies have established that the SVA retrotransposon insertion in TAF1 causes XDP, 19,20 the pathogenic mechanisms linking this genetic etiology to neurodegeneration in this rare disease remain unsettled. An essential clue to this longstanding issue was the observation that a polymorphic hexanucleotide repeat within this pathogenic insertion correlates with clinical disease manifestation and somatically expands in patients' brains, 8,9,14,15 implying that XDP may share causal pathways with other diseases caused by unstable repeat expansions. 16 By developing XDP-specific RAN translation reporters, our work provides the first in-vitro proof of principle that the XDP-associated hexanucleotide repeat is translated into proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, TAF1 LoF in rodents' brains failed to recapitulate the specific pattern of striatal neurodegeneration in this rare disease 12,13 . Moreover, somatic expansions of the hexanucleotide repeat mentioned above were found to occur at greater levels in the brain relative to the blood of XDP patients, hinting at the possible contribution of other repeat‐mediated pathogenic processes in XDP 14‐16 . This study investigated the potential of the XDP‐linked (AGAGGG) n repeat expansion to undergo RAN translation as a possible contributor to disease pathogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Alan Mejia Maza.…”
Section: Correction To: Acta Neuropathologica Communications (2022) 1...mentioning
confidence: 99%